Control strategies in the spatial population dynamics of Aedes aegypti vector using sterile mosquitoes and insecticides - Carmen Alicia Ramírez Bernate; Héctor Jairo Martínez Romero; Diana Marcela Erazo Borja (Universitas Scientiarum)
In this work, we analyze the population dynamics of the Aedes aegypti mosquito, a transmitter of various viruses such as dengue, zika, and chikungunya, in a given area, based on the use of various control techniques. To do this, we use a reaction-diffusion model that considers various environmental characteristics such as temperature and landscape shape. Initially, we do this analysis using larvicides, insecticides, and the SIT (sterile insect release) technique separately. We simulate different control scenarios using appropriate numerical methods, test combinations of these techniques, and determine the efficiency of each strategy according to the overall reduction in the number of fertilized females due to the applied technique. Subsequently, through a cost-effectiveness analysis, we verified that the release of sterile mosquitoes at the beginning of each seasonal period is the best strategy to control the population of Aedes aegypti.